2019
DOI: 10.33512/jat.v12i1.5538
|View full text |Cite
|
Sign up to set email alerts
|

Partisipasi Petani Dalam Kegiatan Penyuluhan Dan Adopsi Pemupukan Padi Sawah Di Kecamatan Kersamanah Kabupaten Garut

Abstract: Peningkatan produksi padi sawah telah dilakukan pemerintah dengan implementasi inovasi teknologi melalui kegiatan penyuluhan yang melibatkan partisipasi petani. Penelitian ini bertujuan menganalisis secara deksriptif partisipasi petani dalam kegiatan penyuluhan dan adopsi pemupukan padi sawah serta menganalisis faktor-faktor yang berhubungan dengan partisipasi petani dalam kegiatan penyuluhan dan adopsi pemupukan padi sawah. Penelitian dilaksanakan di Kecamatan Kersamanah Garut. Sampel penelitian sebanyak 87 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
0
6
1
7
Order By: Relevance
“…Maryani et al (2017), Anwarudin (2017) and Liani et al (2018) emphasized that participation has been proven to strengthen institutions. Anwarudin and Maryani (2017) and Putri et al (2019) added that participation includes participation in planning, implementation and evaluation. Anwarudin and Dayat (2019) reported that participation is a determining factor in the sustainability of agricultural businesses.…”
Section: Tabel 2 the Results Of The Statistical Analysis Of Factors mentioning
confidence: 99%
“…Maryani et al (2017), Anwarudin (2017) and Liani et al (2018) emphasized that participation has been proven to strengthen institutions. Anwarudin and Maryani (2017) and Putri et al (2019) added that participation includes participation in planning, implementation and evaluation. Anwarudin and Dayat (2019) reported that participation is a determining factor in the sustainability of agricultural businesses.…”
Section: Tabel 2 the Results Of The Statistical Analysis Of Factors mentioning
confidence: 99%
“…Intensity Counseling tends to be carried out routinely every 2 weeks. The implementation of the counseling according to Putri et al, (2019) was in accordance with the standard of training and visits that had lasted a long time.…”
Section: External Factorsmentioning
confidence: 99%
“…Information that is often sought for includes new high yielding seeds, how to control pests and diseases, and selling prices. Innovations that are often sought include planting, fertilizing, and integrated pest control in harmony with the report Putri et al, (2019).…”
Section: Relationship Between Internal External Leadership Roles and The Effectiveness Of Farmer Groupsmentioning
confidence: 99%
“…Oleh karena itu perlu adanya upaya peningkatan pengetahuan, sikap, dan keterampilan petani tentang pemupukan dan bahan pupuk kimia yang berlebihan dan ramah lingkungan melalui penggunaan asam humat untuk mengefisiensika penggunaan pupuk dan membenahi tanah. Efisiensi pemupukan tidak hanya berperan penting dalam meningkatkan produksi dan pendapatan petani, tetapi juga terkait dengan keberlanjutan sistem produksi (Putri et al 2019).…”
Section: Pendahuluanunclassified